4. ECONOMIC ASYMMETRY IN DRONE WARFARE A CASE STUDY OF IRAN'S SHAHED-136 OPERATION AGAINST ISRAEL'S IRON DOME DEFENSE SYSTEM - Ahmad Ilham Kamal; Muchammad Furqon Muchaddats; Ferdy Anggrian; Andromeda Yoga Pratama; Riza Suseno; Kurniawan; Dikasitama (Jurnal TNI Angkatan Udara, 2026)
The advent of low-cost loitering munitions has revolutionized modern warfare,creating a profound economic imbalance between offensive and defensive capabilities. In theMiddle East, the deployment of Iran's Shahed-136 drone against Israel's Iron Dome defensesystem serves as a prime example of a "cost-imposing" strategy in asymmetric warfare.Objective: This study aims to quantify the economic disproportion between the production anddeployment costs of the Shahed-136 drone and the operational costs of the Iron Domesystem. It explores how this cost ratio impacts long-term national defense budgets andstrategic sustainability. Methodology: This study uses a qualitative-descriptive approachsupported by comparative economic modelling. Data are synthesized from defense budgetreports, estimates of the Shahed-136 manufacturing costs, and the unit cost of the Iron DomeTamir interceptor missile. The analysis uses the Cost-Exchange Ratio (CER) to evaluate theeconomic efficiency of both sides. Results: The study's findings reveal a sharp economicasymmetry, with a single Shahed-136 estimated to cost between $20,000 and $50,000,depending on configuration, while a single Tamir interceptor missile costs approximately$40,000 to $100,000, depending on configuration. When factoring in "saturation attacks" (ordrone swarms), defense costs increase exponentially, not only through missile expenditurebut also through the economic disruption caused by airstrike warnings and collateralinfrastructure damage if interceptions fail. Conclusion: The study concludes that while IronDome remains tactically effective in saving lives, its current economic trajectory isunsustainable against the threat of low-cost, mass-produced drones. The study suggests thatto maintain strategic stability, the defense framework must transition to lower-cost interceptiontechnologies, such as directed energy weapons (lasers/Iron Beam), to neutralize theeconomic advantage currently held by offensive drone platforms.